A modified three-port "hidden scars" surgical approach in gynecology: A surgeon's experience of an initial 72 cases - Felix Wu Shun Wong; Eric Tat Choi Lee (Wolters Kluwer Medknow Publications, 2014)
Objective: The study objectives were to determine the surgical outcomes of a personal series of gynecological patients treated with a modified three-port "hidden scars" surgical approach (HS surgical approach) for the treatment of benign gynecological diseases. Study design: This was a retrospective series performed by one of the study authors FW to analyze 72 women treated with a modified three-port HS approach for the treatment of benign gynecological diseases from January 2013 to August 2013. Results: Patients' characteristics, pathology, outcome, and gynecologic procedures performed using this HS approach are presented. The surgical procedures included 34 laparoscopic adnexal ovarian and tubal surgeries, 28 laparoscopic hysterectomy (including pelvic lymphadenectomy for the treatment of uterine cancer in 1 patient), eight laparoscopic myomectomy, one laparoscopic adhesiolysis, and one laparoscopic excision of severe pelvic endometriosis. Laparoscopic myomectomy and excision of advanced pelvic endometriosis took longer time to perform with this approach, but there was no significant difference in the amount of blood loss and length of stay in the hospital. There was no perioperative complication in this personal series. Conclusion: The HS approach in gynecological surgery is feasible, safe, and reproducible when applied in women with gynecological diseases. The operation time, length of stay, and outcome would be comparable to conventional laparoscopic surgery.